A search for the variation of speed of light using galaxy cluster gas mass fraction measurements - Mendonça, I. E.C.R.; Bora, Kamal; Holanda, R. F.L.; Desai, Shantanu; Pereira, S. H. [UNESP] (IOP Publishing, 2021)
In this paper, we implement a new method to test the invariance of the speed of light (c) as a function of redshift, by combining the measurements of galaxy cluster gas mass fraction, H(z) from cosmic chronometers, and Type-Ia supernovae (SNe Ia). In our analyses, we consider both a constant depletion factor (which corresponds to the ratio by which the cluster gas mass fraction is depleted with respect to the universal baryonic mean) and one varying with redshift. We also consider the influence of different H 0 estimates on our results. We look for a variation of c, given by c(z) = c 0(1+c 1 z). We find a degeneracy between our final results on c variation and the assumptions on the gas mass fraction depletion factor. Most of our analyses indicate negligible variation of the speed of light.
Keywords: cosmology of theories beyond the SM; galaxy clusters; supernova type Ia-standard candles